Gallilei covariant quantum mechanics in electromagnetic fields. (1985) - Wilhelm, H. E.
Abstract : A formulation of the quantum mechanics of charged particles in time-dependent electromagnetic fields is presented, in which both the Schroedinger equation and wave equations for the electromagnetic potentials are Galilei covariant, it is shown that the Galilean relativity principle leads to the introduction of the electromagnetic substratum in which the matter and electromagnetic waves propagate. The electromagnetic substratum effects are quantitatively significant for quantum mechanics in reference frames, in which the substratum velocityw is in magnitude comparable with the velocity of lightc . The electromagnetic substratum velocityw occurs explicitly in the wave equations for the electromagnetic potentials but not in the Schroedinger equation.